NO CHANGES TO HOSPITAL USM SERVICE CHARGES DESPITE GST - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 1 April 2015 The Hospital USM (HUSM) at the Health Campus in Kelantan has yet to impose additional service charges on patients even as the Goods and Services Tax (GST) comes into effect today.